Multi detector computed tomography imaging in penetrating injuries - Sachdev, Namrita; Singh, Yashvant; ., Sana; Mehta, Dipshi (International Journal of Research in Medical Sciences, 2020)
Background: Penetrating injuries forms an important component of surgical emergencies. Penetrating trauma typically involves the violation of the body by a gunshot wound (GSW) or stab wound. Emergency laparotomy is the accepted management in patients with a penetrating injury who are not hemodynamically stable. However, selective non-operative management has been shown to decrease the rate of unnecessary surgery. Plain radiographs and FAST are useful for initial assessment of these patients. Multi detector CT is an indispensable tool in the evaluation of patients who are stable and are candidates for conservative treatment. Methods: A cross sectional observational study was carried out on 40 patients admitted with penetrating injury to the trauma centre of PGIMER and Dr RML hospital. Of the 40 patients, 14 were taken for emergency laparotomy. In 26 cases, MDCT was done to evaluate for solid organ, hollow organ and vascular injuries. Results: The mean age of patients was 38 years, with male to female ratio of 5:1. Stab injury was the commonest type of injury, followed by gunshot wounds. Liver was the commonest solid organ involved, followed by kidneys and spleen. Other organs involved were diaphragm, small bowel and colon. Conclusions: Penetrating injuries can be life-threatening, making prompt diagnosis essential. Recognizing key abnormalities on MDCT ensures patients are triaged appropriately. Multi-detector CT is thus widely used to evaluate penetrating injuries in stable patients.